2012
DOI: 10.1111/j.1365-2133.2012.11083.x
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinomas without histological confirmation and their treatment: an audit in four European regions

Abstract: SummaryBackground Limited data are available on how often basal cell carcinomas (BCCs) are clinically diagnosed without histological confirmation and how they are treated. Objectives Within the framework of the EPIDERM project, an audit was conducted in four European countries to study the occurrence of clinically diagnosed BCCs without histological confirmation and to investigate how these are treated. Methods In the Netherlands, Scotland, Finland and Malta studies were performed within different timeframes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
0
25
0
2
Order By: Relevance
“…This problem is almost non‐existent for melanoma and SCC, because these cutaneous malignancies have a higher metastatic potential than BCC and are usually surgically treated and histologically confirmed. A recent European study observed that only 0.7–24.1% of the subsequent BCCs in patients with a prior BCC were clinically diagnosed, indicating that the degree of underestimation of our data is relatively limited, but country‐specific . The risk estimate proportion was the most frequently reported estimate in the literature describing risks of subsequent cutaneous malignancies, but has the disadvantage that it does not control for the background incidence in the general population and it is not time‐specific nor does it account for the competing risk ‘death’.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This problem is almost non‐existent for melanoma and SCC, because these cutaneous malignancies have a higher metastatic potential than BCC and are usually surgically treated and histologically confirmed. A recent European study observed that only 0.7–24.1% of the subsequent BCCs in patients with a prior BCC were clinically diagnosed, indicating that the degree of underestimation of our data is relatively limited, but country‐specific . The risk estimate proportion was the most frequently reported estimate in the literature describing risks of subsequent cutaneous malignancies, but has the disadvantage that it does not control for the background incidence in the general population and it is not time‐specific nor does it account for the competing risk ‘death’.…”
Section: Discussionmentioning
confidence: 79%
“…13 The pooled risk estimates presented for a BCC after a melanoma are probably underestimated, because some BCCs may be diagnosed clinically without histological confirmation. 42 This problem is almost non-existent for melanoma and SCC, because these cutaneous malignancies have a higher metastatic potential than BCC and are usually surgically treated and histologically confirmed. A recent European study observed that only 0.7-24.1% of the subsequent BCCs in patients with a prior BCC were clinically diagnosed, indicating that the degree of underestimation of our data is relatively limited, but country-specific.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…4 Surgery is still considered the first-line treatment in different European countries, and 57-87% of all BCCs are still treated by standard excision (SE). [5][6][7][8] In the current observational literature, 5-year recurrence rates for Mohs micrographic surgery (MMS) are reported to be 1Á0-6Á5% for primary BCC and 4Á0-10Á0% for recurrent tumours. 9-15 A large, 10-year followup randomized controlled trial of high-risk facial BCCs showed a difference of 7Á8% for primary and 9Á6% for recurrent BCCs in favour of MMS over SE, although only the latter reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is often omitted from official cancer statistics, as little is known about the true extent of the disease. Cancer registries, if at all, only include histologically confirmed tumours and do not take into account the substantial proportion of BCCs diagnosed clinically without histology (Flohil et al , 2012). …”
mentioning
confidence: 99%